Pengaruh Pengendalian Diri, Self Confidence, Motivasi dan Minat Belajar Terhadap Tingkat Pemahaman Akuntansi (Studi pada Mahasiswa Akuntansi Universitas Brawijaya dan Universitas Islam Malang) - Chori’ah Wahyu Yulianingsih; Moh. Amin; Dewi Diah Fakhriyyah (Universitas Islam Malang, 2023)
The purpose of this study is to examine the effects of self control, self confidence, motivation, and interest in learning on accounting simultaneously or partially. The population in this study were accounting students class of 2019 from two public and private universities in Malang, namely Malang Islamic University and Brawijaya University. This study is categorized as a quantitative study, and the method used to collect the data is a survey, namely by distributing questionnaires to 220 respondents who are determined as samples. In determining the sample, the researcher used a purposive sampling technique using the Slovin formula. The data analysis method in this research is using multiple linear regression test, and the tests used are descriptive statistical tests, instrument tests, normality tests, classical assumption tests and hypothesis testing. The results of this study indicate that simultaneously self control, self confidence, motivation and interest in learning have a significant effect on the level of understanding of accounting. Partially self control, self confidence, motivation and interest in learning have a significant effect on the level of understanding of accounting.Keywords: Self control, self confidence, motivation, interest in learning, level of accounting understanding